PKM2 Drives Hepatocellular Carcinoma Progression by Inducing Immunosuppressive Microenvironment - Li, Tian-En; Wang, Shun; Shen, Xiao-Tian; Zhang, Ze; Chen, Mo; Wang, Hao; Zhu, Ying; Xu, Da; Hu, Bei-Yuan; Wei, Ran; Zheng, Yan; Dong, Qiong-Zhu; et al. (Frontiers in Immunology, 2020)
Background and Aims: Pyruvate kinase M2 (PKM2) is an essential regulator of the Warburg effect, but its biological function promoting immune escape of hepatocellular carcinoma (HCC) is unclear. Methods: GEPIA web tool and immunohistochemistry (IHC) analysis were employed to evaluate the clinical relevance of PKM2 in HCC patients. Both in vitro CCK-8, colony formation, and transwell assays, and in vivo xenografts were performed to evaluate the malignancy of HCC cells. PKM2 and PD-L1 levels were examined by Western blot, qRT-PCR and IHC. The role of PKM2 on in vivo immune response was also investigated. Results: PKM2 was significantly upregulated in HCC and associated with a poor prognosis of HCC patients. Knockdown of PKM2 inhibited in vitro proliferation, migration, and invasion of HCC cells, as well as in vivo tumor growth. Strikingly, PKM2 showed a strong correlation with the expression of immune inhibitory cytokines and lymphocyte infiltration in HCC. The overexpression of PKM2 sensitized HCC to immune checkpoint blockade, which enhanced IFN-γ positive CD8 T cells in HCC mice models. Conclusion: PKM2 might be a predictor and a potential therapeutic target for immune checkpoint inhibitors in HCC.